Thrombolysis in Mild Stroke: A Comparative Analysis of the PRISMS and MaRISS Studies. Issue 10 (October 2021) - Asdaghi, Negar; Romano, Jose G.; Gardener, Hannah; Campo-Bustillo, Iszet; Purdon, Barbara; Khan, Yosef M.; Gulati, Deepak; Broderick, Joseph P.; Schwamm, Lee H.; Smith, Eric E.; Saver, Jeffrey L.; Sacco, Ralph; et al.
Abstract : Background and Purpose: Mild ischemic stroke patients enrolled in randomized controlled trials of thrombolysis may have a different symptom severity distribution than those treated in routine clinical practice. Methods: We compared the distribution of the National Institutes of Health Stroke Scale (NIHSS) scores, neurological symptoms/severity among patients enrolled in the PRISMS (Potential of r-tPA for Ischemic Strokes With Mild Symptoms) randomized controlled trial to those with NIHSS score ⩽5 enrolled in the prospective MaRISS (Mild and Rapidly Improving Stroke Study) registry using global P values from χ 2 analyses. Results: Among 1736 participants in MaRISS, 972 (56%) were treated with alteplase and 764 (44%) were not. These participants were compared with 313 patients randomized in PRISMS. The median NIHSS scores were 3 (2–4) in MaRISS alteplase-treated, 1 (1–3) in MaRISS non–alteplase-treated, and 2 (1–3) in PRISMS. The percentage with an NIHSS score of 0 to 2 was 36.3%, 73.3%, and 65.2% in the 3 groups, respectively ( P <0.0001). The proportion of patients with a dominant neurological syndrome (≥1 NIHSS item score of ≥2) was higher in MaRISS alteplase-treated (32%) compared with MaRISS nonalteplase-treated (13.8%) and PRISMS (8.6%; P <0.0001). Conclusions: Patients randomized in PRISMS had comparable deficit and syndromic severity to patients not treated with alteplase in the MaRISS registry and lesser severity than patients treated with alteplase in MaRISS. The PRISMS trial cohort is representative of mild patients who do not receive alteplase in current broad clinical practice. Abstract : Supplemental Digital Content is available in the text.